2009
DOI: 10.1159/000209396
|View full text |Cite
|
Sign up to set email alerts
|

Syncytin-1 and Glial Cells Missing a: Hypoxia-Induced Deregulated Gene Expression along with Disordered Cell Fusion in Primary Term Human Trophoblasts

Abstract: Background/Aims: Pre-eclampsia, a major cause of perinatal morbidity, is characterized by alterations in placental oxygen availability and trophoblast differentiation. We investigated how different levels of hypoxia alter the expression of syncytin-1, glial cells missing a (GCMa) and syncytin-1 receptor ASCT2 and affect syncytialization in primary term human trophoblasts. Methods: Cells were incubated at 1, 3, 6 and 21% O2 for 24, 48 and 72 h with or without cyclic adenosine monophosphate (cAMP). Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 78 publications
(55 reference statements)
4
19
0
Order By: Relevance
“…Human CTs were isolated using the trypsin-DNase-dispase-collagenase-hyaluronidase/percoll method [16], [50][53] from 3 independent control, 3 IUGR, 3 PE, 3 PE/IUGR and 2 HELLP/IUGR placentae. For quality control see Ruebner et al [16].…”
Section: Methodsmentioning
confidence: 99%
“…Human CTs were isolated using the trypsin-DNase-dispase-collagenase-hyaluronidase/percoll method [16], [50][53] from 3 independent control, 3 IUGR, 3 PE, 3 PE/IUGR and 2 HELLP/IUGR placentae. For quality control see Ruebner et al [16].…”
Section: Methodsmentioning
confidence: 99%
“…The support of syncytiotrophoblast formation at 20% but not 1% O 2 has been reported in first and third trimester cytotrophoblasts, but alternate lineage choice or intracellular enzymatic regulation of the process was not studied 68, 69 . It has been reported that glycogen synthase kinase (GSK)3 increase and phosphoinositol 3 kinase (PI3K-Akt) activity decrease is causal for hypoxia-induced Gcm1 protein degradation also at 1% O 2 which also occurs in hypoxia associated preeclampsia 23 .…”
Section: Discussionmentioning
confidence: 99%
“…9 Syncytin expresses on mouse syncytiotrophoblasts, 10 induces trophoblast fusion during placental development, 11,12 and contributes to PE pathogenesis. 13,14 Blood samples collected at the baseline, 17-18 dpc, and postpartum using 3.8% of sodium citrate as an anticoagulant were centrifuged at 1500×g for 20 min at 25°C to collect platelet-poor plasma (PPP). PPP was incubated with a FITC-conjugated polyclonal syncytin antibody (FabGennix International Inc., Frisco, TX) for 30 min at room temperature and analyzed using flow cytometry (Beckon Dickinson, San Jose, CA).…”
Section: Flow Cytometrymentioning
confidence: 99%